The Effect of Technical Skills on Employee Productivity of PT Sumber Bara Abadi Through Work Environment As a Moderator Variable - Reny Ramahdani; Vera Anitra; Achmad Efendi (International Journal of Economics and Management Research, 2025)
Employee productivity is a crucial element in determining the operational success of a company, which is influenced by internal factors such as technical skills and working conditions. The purpose of this study is to examine the extent to which technical skills contribute to increasing employee productivity at PT Sumber Bara Abadi, considering the role of the work environment as a mediating variable. The research approach is quantitative, using the Structural Equation Modeling (SEM) method with the Partial Least Squares (PLS) technique. The population in this study includes all 70 permanent employees of the company, where the entire population was used as the sample through a census technique due to its limited size. Data collection was conducted using a questionnaire designed to assess aspects of technical skills, work environment, and productivity levels. The analysis results indicate that technical skills have a positive and significant influence on productivity, as well as on the work environment. Additionally, the work environment was also found to have a significant impact on employee productivity. Other findings confirm that technical skills indirectly influence productivity through the mediation of the work environment. Based on these results, it is recommended that the company develop a technical skills training program integrated with a strategy for creating a conducive work environment to promote optimal and sustainable productivity.